Early discharge using single cardiac troponin and copeptin testing in patients with suspected acute coronary syndrome (ACS): a randomized, controlled clinical process study - Möckel, Martin; Katus, Hugo; Giannitsis, Evangelos (European heart journal, 2015)
Aims: This randomized controlled trial (RCT) evaluated whether a process with single combined testing of copeptin and troponin at admission in patients with low-to-intermediate risk and suspected acute coronary syndrome (ACS) does not lead to a higher proportion of major adverse cardiac events (MACE) than the current standard process (non-inferiority design). Methods and results: A total of 902 patients were randomly assigned to either standard care or the copeptin group where patients with negative troponin and copeptin values at admission were eligible for discharge after final clinical assessment. The proportion of MACE (death, survived sudden cardiac death, acute myocardial infarction (AMI), re-hospitalization for ACS, acute unplanned percutaneous coronary intervention, coronary artery bypass grafting, or documented life threatening arrhythmias) was assessed after 30 days. Intention to treat analysis showed a MACE proportion of 5.17% [95% confidence intervals (CI) 3.30-7.65%; 23/445] in the standard group and 5.19% (95% CI 3.32-7.69%; 23/443) in the copeptin group. In the per protocol analysis, the MACE proportion was 5.34% (95% CI 3.38-7.97%) in the standard group, and 3.01% (95% CI 1.51-5.33%) in the copeptin group. These results were also corroborated by sensitivity analyses. In the copeptin group, discharged copeptin negative patients had an event rate of 0.6% (2/362). Conclusion: After clinical work-up and single combined testing of troponin and copeptin to rule-out AMI, early discharge of low- to intermediate risk patients with suspected ACS seems to be safe and has the potential to shorten length of stay in the ED. However, our results need to be confirmed in larger clinical trials or registries, before a clinical directive can be propagated.